Patella Alta in Cerebral Palsy - Satake, Takayuki; Shibata, Naoyuki; Morinaga, Masahiro; Takami, Hiroaki (Orthopedics & Traumatology, 1988)
The incidence and degree of patella alta were studied radiographically in 22 ambulatory CP, 16 nonambulatory CP and 14 normal children. The relationship between the degree of patella alta and other factors (“spasticity score”, popliteal angle and true knee contracture) were analysed. The results were as follows: 1) The incidence of patella alta in CP group were higher than that in normal. 2) The degree of patella alta and “spasticity score” were correlated in non-ambulatory CP group (γ=0.37). 3) The presence of patella alta and that of true knee contracture were correlated in ambulatory CP and non-ambulatory CP groups.